2012
DOI: 10.4172/2161-105x.1000118
|View full text |Cite
|
Sign up to set email alerts
|

Serum KL-6 Levels in Patients with Lung Cancer

Abstract: Background: Serum levels of KL-6 are widely used as an indicator of activity of interstitial lung disease. Although KL-6 was initially developed as a serum marker for malignancies, it is still unknown if KL-6 can be used as a biological marker of lung cancer. This study aimed to determine the positive rate of KL-6 in patients with lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…However, an increase in KL-6 does not always indicate the presence of IP. Yoshimatsu et al reported that KL-6 levels could increase by the existence of lung cancer itself, with a significant association with tumor size [ 10 ]. Several cases showed high pre-treatment KL-6 levels, although they did not have pre-existing IP (the bottom right example in Fig 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an increase in KL-6 does not always indicate the presence of IP. Yoshimatsu et al reported that KL-6 levels could increase by the existence of lung cancer itself, with a significant association with tumor size [ 10 ]. Several cases showed high pre-treatment KL-6 levels, although they did not have pre-existing IP (the bottom right example in Fig 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, prescreening of KL-6 is suggested to decide the strategy for SABR in lung cancer patients [ 5 7 ]. However, since KL-6 is associated with RP+ as well as the existence of lung cancer itself [ 10 , 11 ], the predictive performance of pretreatment KL-6 may not be sufficient ( S1 Table ).…”
Section: Introductionmentioning
confidence: 99%
“…KL-6 was first suggested as a serum biomarker for lung, breast and pancreatic cancers. In lung cancer, its serum levels could indicate malignancy progression 20 . However, KL-6 showed a lower diagnostic accuracy than other tumor markers, such as carcinoembryonic antigen, a reliable predictor of treatment response in NSCLC 21 .…”
Section: Peripheral Biomarkers Of Ipf and Lung Cancermentioning
confidence: 99%